2012
DOI: 10.1021/nl301709x
|View full text |Cite
|
Sign up to set email alerts
|

Glancing Angle Deposition of Copper Iodide Nanocrystals for Efficient Organic Photovoltaics

Abstract: We report a simple method to achieve efficient nanostructured organic photovoltaics via patterning copper iodide (CuI) nanocrystals on indium tin oxide by glancing angle deposition. The strong interfacial interaction between zinc phthalocyanine (ZnPc) and CuI leads to the formation of nanopillar arrays with lying-down molecular order, which greatly improve light absorption and surface roughness for exciton dissociation. Optimized ZnPc/C(60) bilayer cell has a power conversion efficiency of 4.0 ± 0.1%, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 40 publications
2
82
0
Order By: Relevance
“…Copper halides are p-type wide-bandgap semiconductors, thin films of which can be prepared by vacuum-or solution-based processes. Because of their compatible energy levels and strong interaction with organic molecules, our previous works have showed that copper halides can act as hole transport layers or structural templates for improving organic photovoltaics [35,36]. Here, we demonstrate the manipulation of halide crystallites in CNT networks at nanoscale by utilizing a pulse photonic curing system.…”
Section: Introductionmentioning
confidence: 96%
“…Copper halides are p-type wide-bandgap semiconductors, thin films of which can be prepared by vacuum-or solution-based processes. Because of their compatible energy levels and strong interaction with organic molecules, our previous works have showed that copper halides can act as hole transport layers or structural templates for improving organic photovoltaics [35,36]. Here, we demonstrate the manipulation of halide crystallites in CNT networks at nanoscale by utilizing a pulse photonic curing system.…”
Section: Introductionmentioning
confidence: 96%
“…The stable cubic structure makes it easy to synthesize CuI thin films near room temperature using a number of chemical and physical methods, including vapor iodization (20), thermal evaporation (27), pulsed laser deposition (PLD) (28), and sputtering (29)(30)(31). Therefore, CuI is readily compatible in organic electronics, for example as (part of) the electrode in organic light-emitting diodes and organic solar cells (32)(33)(34). Recent work on the roomtemperature heteroepitaxy of CuI demonstrates its compatibility…”
mentioning
confidence: 99%
“…This increase in donor-acceptor interface area was consistent with the 10% improvement that was observed in the J sc . Therefore, the higher J sc of IHJ OPV (30-min treatment) was caused by increased interface area [22,23], while the higher FF was caused by increased charge transport ability within the nanocrystallized C 60 films [27]. The durability of the IHJ OPVs that contained the interpenetrating nanocrystallized C 60 films treated for 30 min was tested under a N 2 atmosphere (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thin-film organic photovoltaic cells (OPVs) have attracted tremendous attention for their promise to provide low cost and light weight devices that can absorb a large proportion of the solar spectrum [1][2][3][4][5][6][7]. OPVs commonly use either a planar heterojunction (PHJ) structure [8,9], which consists of donor-acceptor bilayer deposition, or a bulk heterojunction (BHJ) structure, which consists of a donor-acceptor mixture as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation